A Mexican State of Mind : New York City and the New Borderlands of Culture - Planas, Melissa Castillo, 1984- (Book collections on Project MUSE., 2020)
A Mexican State of Mind: New York City and the New Borderlands of Culture explores the cultural and creative lives of the largely young undocumented Mexican population in New York City since September 11, 2001. Inspired by a dialogue between the landmark works of Paul Gilroy and Gloria Anzaldúa, it develops a new analytic framework, the Atlantic Borderlands, which bridges Mexican diasporic experiences in New York City and the black diaspora, not as a comparison but in recognition that colonialism, interracial and interethnic contact through trade, migration, and slavery are connected via capitalist economies and technological developments. This book is based on ten years of fieldwork in New York City, with members of a vibrant community of young Mexican migrants who coexist and interact with people from all over the world. It focuses on youth culture including hip hop, graffiti, muralism, labor activism, arts entrepreneurship and collective making.